2010
DOI: 10.3174/ajnr.a2168
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic CT after Intravenous Contrast Agent Application: A Noninvasive Follow-Up Tool after Intracranial Angioplasty and Stenting

Abstract: BACKGROUND AND PURPOSE:ICAS is one of the therapeutic options in symptomatic cerebral artery stenosis. iaDSA is the current criterion standard examination after ICAS for the detection of ISR. In this study, we evaluated ivACT as a potential noninvasive follow-up alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
2
22
0
1
Order By: Relevance
“…In an animal model, CA-CTA correlated well with the visualization of stents compared to DSA, while conventional MS-CTA failed to visualize the lumen of the stent device (8). In a phantom study and a small case series, Psychogios et al demonstrated that CA-CTA was comparable to DSA in the recognition and quantification of in-stent re-stenosis (9,18). These promising findings in patients were confirmed by others using an optimized image protocol (15).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In an animal model, CA-CTA correlated well with the visualization of stents compared to DSA, while conventional MS-CTA failed to visualize the lumen of the stent device (8). In a phantom study and a small case series, Psychogios et al demonstrated that CA-CTA was comparable to DSA in the recognition and quantification of in-stent re-stenosis (9,18). These promising findings in patients were confirmed by others using an optimized image protocol (15).…”
Section: Discussionsupporting
confidence: 63%
“…In vitro studies of small vessel stents demonstrated that the minimum diameter of stents for reliable visualization of the lumen using MS-CTA was 4.0 mm (1,11,12). There are only small case series in patients available that seem to confirm the results of these in vitro studies (9).…”
Section: Discussionsupporting
confidence: 55%
“…Recent studies have shown the potential of IV-ACT in the delineation of even small-sized (2-or 3-mm diameter) intracranial stents and the accurate depiction of in-stent restenosis, compared with IA-DSA. 23 In the postcoiling evaluation of intracranial aneurysms, ACT proved to be a useful addition to conventional IA-DSA. 24 The ability of ACT to produce thin cross-sectional images with approximately 0.2-mm section thickness is also valuable in the characterization of spinal dural arteriovenous fistulas.…”
mentioning
confidence: 99%
“…4,28,29 However, no objective data analysis has been performed on the reliability of IV FDCT with DSA as a reference. Furthermore, previous studies compared stenotic lesions using different radiologic methods within 30 days.…”
Section: 12mentioning
confidence: 99%